Epidemiologi Pemakaian Obat Peranannya Want Peningkatan Kualitas Pelayanan Kesehatan - Budiono Santoso, Budiono Santoso (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1988)
Drug utilization has been defined as "the marketing, distribution, prescription and use of drugs in a society, with special emphasis on the resulting medical, social and economic consequences". The aim of drug utilization study is to achieve optimal use of drugs in a society, i. e. safe, efficacious, rational and cost-effective. Various benefits can be obtained from drug utilization study which by all means may increase the quality of patient care.Drug utilization study may be classified into two types based on its specific aim. First routine monitoring of drug use in a society which is aimed at examining the general pattern of drug use and predicting the forthcoming trends, and second special drug utilization study which is aimed at investigating specific study questions and hypothesis.Review of the pattern of drug utilization is likely becoming and effective feedback to the prescribers and drug policy makers towards more rational use of drugs.Key Words: drug utilization - patient care - drug policy - pharmacoepidemiology - drug abuse